Clinical Appearance Of Tinea Corporis Resembles With Tinea Imbricata And Condyloma Acuminata Genital In A Reproductive Woman With HIV : A Case Report - Kencana, Indah; Ariani, Tutty; Anum, Qaira; Rizal, Yosse (Andalas Obstetrics And Gynecology Journal, 2021)
Background: HIV (human immunodeficiency virus) is a virus that attacks the body’s immune system that can cause immunodeficiency. Immunodeficiency results in increased susceptibility to fungal infections. The other opportunistic infection, condyloma acuminate is prevalent in groups at high risk for HIV acquisition and in HIV-infected individuals. Case: There were ring-shaped reddish patches with scaly and itchy on the right back since 3 weeks ago. Patients often scratch it especially when sweating and hot weather. The itchy reddish patches with scaly were increased in number and size on the right back then spreading over the edge to form ring-like patches. Patient complained ring-shaped reddish patches getting more red, scaly, itchy, and wider. 6 months ago, there was a lump that sometime felt itchy in below part of vulva. Patient in reproductive age and not married yet, but sexually active. Patient had a sexual relation with male who HIV 2 years ago. Patient also suffered HIV and got ARV since 6 month ago. There was no protection (condom) during the sexual intercourse. Dermatologic state in right back with efflorescence is plaque erythema with annular concentric ring forms, scale, and blackish crust. Venereologycal state show vegetation in vulva with size 0,2 - 1,5 x 1 x 0,5 cm with verrucous surface. Acetowhite test is positive result. KOH 10% of skin scrapping show fungal element and fungal culture result is tricophyton rubrum. Patient was diagnosed tinea corporis (TC) and condyloma acuminata (CA) genital griseovulfin 900 mg, cetirizin 10 mg, ketokonazol 2% cream twice a day, tricholoroacetat 90% and showed good improvement.Discussion: Diagnosis tinea corporis and CA genital based on clinical findings and mycological examination. Early diagnosis and proper treatment are important in HIV patients in order to prevent severe infection. After 4 weeks treatment, show improvement on TC however CA lesion no reduced. Keywords: tinea corporis,condyloma acuminate, tinea imbricata, HIV, Reproductive age